Pengaruh Kompensasi, Lingkungan dan Budaya Manajemen Terhadap Hasil Kerja Pegawai di Kantor BPJS - Sri Indrayanti; Rahmani Fitra; Ade Suryana; Jana Sandra (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2024)
The aim of this research is to determine the influence of funds, performance and institutional management on BPJS Jakarta branch employees. Technique in determining the impact on workers is by sampling where the takers are 44 samples of personnel from the population in the office agency. The researcher tried to conduct a quantitative descriptive analysis through the measurement of the linkert scale. The method in determining and analyzing the researcher's data used questions from the researcher for all employees of BPJS Ketenagakerjaan Jakarta Kebon Sirih Branch as many as 44 persons. The data was tested using IBM SPSS 25, it showed that the value of the determination coefficient (Adjusted R Square) was 0.717. In addition, there is a Model Feasibility Test (Test F) with a p-value of < significance of 0.05 so that this study is very interesting to analyze what is the impact of this. The results of the study show that there is a good and significant impact on workers at the BPJS Jakarta Branch office It is recommended that other researchers make adjustments by taking other studies so that they can get to know things that can provide interest and motivation in working for workers in an agency.